Imperative Seasoning Characteristics of Yushania alpina (Highland Bamboo) Culms Grown in Dire-Inchini, Ethiopia - Gemechu Kaba; Mahadi Mussa; Getachew Desalegn; Anteneh Tesfaye; Tsegaye Wubishet; Getachew Mezgebu (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
Bamboo is the world's fastest-growing plant and the finest conceivable substitute for future wood. It has a wide range of applications, from traditional use to industrial manufacture in many countries. Bamboo has been traditionally used in Ethiopia for the construction of huts and fencing, furniture, containers, beehives, and other small-scale objects. Lack of proper processing practices such as seasoning among the reasons for its low use. When bamboo culms are not properly seasoned, they have a high split and shrinkage rate that led to biological and physical degradations. 3–5year-old samples of Yushania alpinia culms were gathered from Dire-Inchni (Oromia Region). After harvesting culms, were cut into three portions (bottom, middle and top) to investigate the imperative characteristics of the material during the drying process. Kiln and air-drying procedures were used to dry the culms. Regression analysis was used to describe the functional relationship between moisture loss in the kiln and air drying. They had an average initial MC 103.67%, final MC 12.33%, and basic density 0.69 g/cm3. Bamboo culms dried in the kiln took 7.7 days to attain about 12 % final MC, while air-seasoned culms took 97 days. proper stacking, drying, and handling is critical for improving the quality, productivity, and service life of bamboo culms-based constructions and goods in the future.